PENGELOLAAN PIUTANG DAGANG UNTUK MENJAGA KETERSEDIAAN KAS USAHA - Ardiansyah Rasyid; Dela Asokawati Puswita Anhar; Elizabeth Christinio Puspita (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
The purpose of this community service activity is to help business owners have knowledge about the management of trade receivables, so that business owners can maintain the availability of cash for operational purposes. The partner chosen in the PKM activity is a packaged seasoning business under the Sasia brand. Sasia MSMEs are domiciled in Tangerang city, Banten Province. Based on initial observations to partners conducted by coming directly to meet with business owners, the main problem lies in the management of trade receivables, especially with the business to business (B2B) customer payment system which buys more goods in installments and not cash. The method offered in the activity is training/socialization on managing trade receivables offline. Through this activity, it is hoped that the accounts receivable problems that arise in the seasoning business will be resolved, and partners can maintain and manage their accounts receivable appropriately. Thus, it is hoped that in the future it will be useful in maintaining the availability of business cash needed by a business.